2005
DOI: 10.4315/0362-028x-68.5.1077
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Salmonella in Retail Meats and Shrimps in the Mekong Delta, Vietnam

Abstract: From March 2000 to September 2001, 608 samples of retail meat (136 pork, 70 beef, 202 chicken, and 200 ducks) and 110 samples of retail shrimp from six provinces of the Mekong Delta in Vietnam were collected individually and examined for the prevalence of Salmonella. Of the 718 samples examined, 243 (33.8%) were Salmonella positive. Salmonella was isolated from 69.9% of the pork samples, 48.6% of the beef samples, 21.0% of the chicken meat samples, 22.3% of the duck meat samples, and 24.5% of the shrimp sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 16 publications
5
28
3
4
Order By: Relevance
“…In the present study in Hung Yen, the Salmonella prevalence in slaughterhouses and markets, with confidence intervals, was within a range of previous reports : from 15.5% to 95.7% 4,10,13) in slaughterhouses, and 33 to 69% 4,12,13) in markets, as mentioned in the introduction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study in Hung Yen, the Salmonella prevalence in slaughterhouses and markets, with confidence intervals, was within a range of previous reports : from 15.5% to 95.7% 4,10,13) in slaughterhouses, and 33 to 69% 4,12,13) in markets, as mentioned in the introduction.…”
Section: Discussionsupporting
confidence: 90%
“…Some previous studies in Vietnam reported that prevalence of Salmonella in pig carcass at slaughterhouse takes wide range from 15% to 95% 4,10,13) . Moreover, Salmonella in pork at market was also reported as a high prevalence which varied from 33 to 69% 4,12,13) . For these reasons, elucidating the dynamics of Salmonella contamination in the pork value chain is urgently required in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Since shellfish are often eaten raw or after minimal cooking, the results illustrate the potential for shellfish also to cause enteric disease. The result for Salmonella contamination in pork samples (64.0%) was in close agreement with that of Phan et al (40), who reported that 69.9% of the retail pork samples were contaminated with Salmonella spp. in the Mekong Delta, Vietnam.…”
Section: Discussionsupporting
confidence: 81%
“…This new clone, which may have emerged only recently, is likely to be found to be prevalent in a single country, possibly Vietnam, where serovar Emek strains have been found in retail meats (33). It has also spread from there to other countries via travelers, though there is no evidence that it has become established in either the United Kingdom or Australia.…”
Section: Discussionmentioning
confidence: 98%